Analysis on the servicescape of shopping mall in Davao City as a determinant for customer response - Salisali, Kent Harvey L. (2023)
Over the years, the industry of retail and commercial spaces has grown significantly and produced important economic benefits for a city. From a strategic standpoint, customer loyalty is considered to be an important factor in a mall?s success. It became the primary focus of marketing campaigns. Moreover, studies have shown that customer satisfaction is an important factor for customer loyalty. Hence, it is important for mall designers to consider how the mall would satisfy the customers based on their expectations. Meanwhile, the concept of servicescape was introduced to study how the physical environment contributes to a person?s behavior. This includes the investigation of tangible elements that help ensure the delivery of high-quality customer services. To help guarantee that the objectives of the shopping mall are met, it is therefore important to evaluate the quality of its servicescape. This study analyzed the effective use of servicescape across different malls in Davao City which were Gaisano Mall of Davao, Abreeza Mall, and SM Lanang Premiere. The study is both quantitative and qualitative in nature. Survey questionnaires were employed to assess the quality of the servicescape across the different areas of each mall. The respondents also ranked the three malls based on their likelihood of visiting that mall again.The results of the study provided a number of design implications that would contribute to the mall?s attractiveness. Based on the findings, servicescape has a significant relationship with customer satisfaction. The ambiance and Natural Environment were two of the highest dimensions of servicescape that contributed to the customer?s satisfaction the most. Therefore, it is important to ensure that the quality of servicescape in shopping malls exhibits a great performance to improve the overall experience of mallgoers and facilitate continuance intention.